Testing Multi-Task Cancer Evolution: How Do We Test Ecological Hypotheses in Cancer? - Plutynski, Anya (Frontiers in Ecology and Evolution, 2021)
Recently Hausser and Alon (2019, 2020) have argued that trade-offs in the evolution of a tumor constrain optimal traits. They describe a set of archetypical gene expression profiles, and represent different cancer types and subtypes as falling within a space of trade-offs between archetypes that maximize the performance of different tasks typically associated with the cancer cell phenotypic profile, sometimes called the “hallmarks” of cancer: "cell division, biomass and energy production, lipogenesis, immune interaction, and invasion and tissue remodeling." On this picture, intertumor heterogeneity can be explained in part as a product of these selective trade-offs at work in different stages of cancer progression, whereas intratumor heterogeneity is due to local variations in selective trade- offs. The aim of this paper is to critically assess this family of models. In particular, to what extent can the inter- and intra-tumor heterogeneity of cancer be explained as a product of selective trade-offs? How much of the heterogeneity we see is a product or byproduct of selection, versus an analogue of "drift"? Are these five "universal" tasks exhaustive? More generally, what are the advantages of this framework, as a heuristic for discovery and prediction, and what are the limits of representing a cancer cell as analogous to an organism, facing selective trade-offs?